Product Design Preferences Using Facial Features And Kansei Engineering - Wan Nor Azman, Wan Ainul Syafika (2021)
In today's aggressive competitive market, to develop a new product that very relevant and match to the consumer' needs and tastes is as a critical issue in the product development. This is due to customers are no more extended hunting down products which fulfill physical requirements (such as function and quality), but they will also to meet their emotional requirements (like feeling and emotion). Thus, to enhance the engaging quality, the company have to launch an attractive product that should fulfil the objectives of individual customer needs. Generally, Kansei Engineering (KE) is used to explore the consumers preferences articulated with their emotional. Through KE it is capable of translating the technology into consumer emotion towards the products that touch the customer emotions and capture the reason of expectations. Furthermore, in order to meet customers’ need towards the product through emotions, the effective way to communicate emotions is also via facial features (physiognomic). Hence, the research goal of this study was to determine the customer preferences towards product design based on KE and individual's facial features (physiognomic). Their preferences are compared and correlated to their individuals' facial features (physiognomic) background as a depiction of their characteristics in their decision making related to the preferences of design product. Moreover, the data collected is through survey by generating the questionnaire. In the process of developing the questionnaire, semantic differential (SD) towards the words (as the expression of feeling or emotion using Kansei) is employed through the affective identification towards the design of product using KE approach. For the validation purpose, the post test survey need to be executed and distributed in order to confirm whether the decision made on the design preferences based on KE and facial features is valid or not. In order to identify the customer's perception level of the products, this research involved 220 respondents (college student) in Universiti Teknikal Malaysia Melaka (UTeM). This study found that Kansei words of Stylish, Comfortable and Elegant has the greatest impact towards the product design. In terms of front view design preferences, Toyota Etios Liva had been selected as the most preferred design under the category of Compact car. While, Peugeot 108 had been choose for side and rear view. Meanwhile, the most preferences design result for Sedan car is BMW f80 for both front and rear view while, Aston Martin S was chosen for side view. This study also found that, there